Geographic information system-based spatial modelling of soil-transmitted helminth infections among preschool-aged children in Masbate, Philippines - Acepcion, Sarah Joy A.; Molina, Victorio B.; Belizario, Jr., Vicente Y.; Co, Kim Carmela D.; Lomboy, Marian Fe Theresa C.; Magtibay, Bonifacio B. (Manila College of Public Health, University of the Philippines Manila, 2021)
Since the effectiveness of the Zero Open Defecation (ZOD) program as a scaling-up approach of the Integrated Helminth Control Program (IHCP) in lowering the rates of Soil-Transmitted Helminth (STH) infections for Preschool-Aged Children (PSAC) has not yet been locally explored, this study aimed to (1) describe the association between environmental determinants and STH cumulative prevalence, and (2) to predict the 2020 STH cumulative prevalence among Preschool-Aged Children in the selected municipalities of Masbate based on the statistically significant environmental determinants using ArcGIS Pro's spatial statistics tool.

A generalized linear regression (GLR) model was used to determine the association of 2014-2015 environmental determinants and observed 2015 STH cumulative prevalence, while a geographically weighted regression (GWR) model was used to produce predicted 2020 STH cumulative prevalence using the 2020 data of statistically significant environmental determinants. ArcGIS' GLR tool with R² of 63% generated a summary output of diagnostic tests and found only 5 out of 20 environmental parameters as statistically significant, while ArcGIS' GWR tool predicted the 2020 STH cumulative prevalence and found only 4 out of 116 barangays hypothetically met the national target of the IHCP for the prevalence of STH infections below 30% in 2020. Results of this Geographic Information System-based spatial analysis revealed that barangays with a moderately low percentage of area with fresh water bodies, a moderately high percentage of households with sanitary toilet and level one water source, and a hundred percent status of ZOD have lower rates of STH cumulative prevalence in PSAC in the selected municipalities in Masbate.
Includes references and appendices. (Missing page 70)
Thesis
Keywords: Geographic information systems; Spatial analysis (Statistics); Soil-transmitted helminthiases; Helminthiasis in children; Preschool children -- Health and hygiene -- Philippines -- Masbate